Clinical and Dermoscopic Approaches to Diagnosis of Frontal Fibrosing Alopecia: Results From a Multicenter Study of the International Dermoscopy Society - Starace, Michela; Orlando, Gloria; Iorizzo, Matilde; Alessandrini, Aurora; Bruni, Francesca; Mandel, Victor Desmond; Awatef, Kelati; Cabo, Horacio; Fabbrocini, Gabriella; Hanane, Baybay; Lanssens, Sven; Lobato-Berezo, Alejandro; et al. (Dermatology Practical & Conceptual, 2022)
Introduction: Frontal fibrosing alopecia (FFA) is a form of primary lymphocytic scarring alopecia characterized by a progressive recession of the fronto-temporal hairline. Although the clinical presentation of FFA is very typical, biopsy for histopathological examination is still recommended to confirm the diagnosis. Currently, a growing number of skin and mucosal inflammatory diseases are diagnosed with modern noninvasive techniques such as dermoscopy without the necessity of a biopsy. Objectives: The International Dermoscopy Society (IDS) aimed to test the ability of its members to diagnose classic FFA through clinical and dermoscopic parameters and to compare acquired data to the largest cohort studies published since 1994. Methods: This is an observational, cross-sectional study describing patient demographics, clinical presentation and diagnostic tools used in a sample of FFA patients collected by IDS members. A literature search was then performed using Pubmed to review studies reporting more than 100 cases. Results: IDS members submitted 188 cases demonstrating a predominant female population (98.4%). In 71.8% of the cases, the clinical presentation and the trichoscopic findings allowed for the diagnosis. Out of 24 revised studies, 13 showed that clinical and trichoscopic features were decisive for the diagnosis in almost all cases. Conclusions: Demographic and clinical data of our cohort were mostly comparable to previous reported data on FFA. The relevant role of the clinical and trichoscopic features in diagnosing FFA was confirmed by our study and the reviewed literature. Trichoscopy could be considered a worldwide-acknowledged non-invasive technique for the diagnosis of FFA.